2015
DOI: 10.1186/s13071-015-0703-y
|View full text |Cite
|
Sign up to set email alerts
|

Density of Aedes aegypti and Aedes albopictus and its association with number of residents and meteorological variables in the home environment of dengue endemic area, São Paulo, Brazil

Abstract: BackgroundMeasure the populations of Ae. aegypti and Ae. albopictus adults according to sex and location inside or outside the residence, estimate Ae. aegypti female density per house and per resident, and test the association with abiotic factors.MethodsAdult mosquitoes were collected monthly with a hand net and portable electric catcher in the peridomiciliary and intradomiciliary premises of residences in an urban area with ongoing dengue transmission in the municipality of São Sebastião, Brazil, from Februa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 40 publications
4
54
0
7
Order By: Relevance
“…Dengue outbreaks have occurred nearly every year in Taiwan since 1987, first appearing in the southern part of Taiwan, which has a high human population density. Dengue outbreaks usually increase during rapid urbanization, and a high human population density has been associated with dengue transmission because of its potential impact on human-mosquito contact [64, 65]. Our study results revealed that the clusters of Ae.…”
Section: Discussionmentioning
confidence: 72%
“…Dengue outbreaks have occurred nearly every year in Taiwan since 1987, first appearing in the southern part of Taiwan, which has a high human population density. Dengue outbreaks usually increase during rapid urbanization, and a high human population density has been associated with dengue transmission because of its potential impact on human-mosquito contact [64, 65]. Our study results revealed that the clusters of Ae.…”
Section: Discussionmentioning
confidence: 72%
“…In Brazil, the number of female Ae. aegypti and rainfall are associated; the correlation is better in peridomiciliary than intradomiciliary premises (Rodriguez et al DENV‐infected mosquitoes were locality‐specific. We found significant interactions between BSN and each of the household and field premises (p=0.00), and between Pasil (p=0.04) and household premises (p=0.04)(Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Three additional variables; persons per house, occupied houses (%) and population density (persons per hectare) were used as indicators of proximity between individuals which can influence Ae. aegypti dynamics and the transmission patterns among residents (Rodrigues et al, 2015;Schmidt et al, 2011). Census data were available for 2010 which coincided with the outbreak in Hermosillo but was two years after the 2008 outbreak in Navojoa.…”
Section: Data Sources and Variablesmentioning
confidence: 99%